The Influence of Edelweis Park Agrotourism Attributes and Service Quality on Tourist Satisfaction and Revisit Intention in The Middle of The COVID-19 - Sukendar, Ni Made Classia; Pitana, I Gde; Surya Diarta, I Ketut (JURNAL MANAJEMEN AGRIBISNIS, 2021)
Edelweis Park Agrotourism is a leading agrotourism developed as a destination tourism attraction in Karangasem Regency. Currently, it is unknown and there is no research that discusses the influence of the attributes of destination attraction and service quality on satisfaction and tourist revisit intention during the COVID-19 pandemic. The purpose of this research were to analyze the influence of the (a) attributes of destination attraction on tourist satisfaction; (b) attributes of destination attraction on tourist revisit intention; (c) service quality on tourist satisfaction; (d) service quality on tourist revisit intention; (e) tourist satisfaction on tourist revisit intention in the middle of the COVID-19 pandemic. The sampling method used was nonprobability sampling with accidental sampling technique using 100 respondents selected by disproportionate stratified random sampling. Results showed that the (a) attributes of destination attraction have a significant and positive effect on tourist satisfaction; (b) attributes of destination attraction have a significant and positive effect on tourist revisit intention; (c) service quality has a significant and positive effect on tourist satisfaction; (d) service quality does not have a significant effect on tourist revisit intention, (e) tourist satisfaction has a significant and positive effect on tourist revisits intention, but the trust variable has a weak moderation variable on tourist satisfaction and revisit intention in the middle of COVID-19 pandemic. Therefore, it is suggested to maintain the attributes of destination attraction, to improve the quality of service, to pay attention to tourist satisfaction, and conduction future research periodically.